The Influence of Fibrin Stabilizing Factor on the Growth of Fibroblats in vitro and Wound Healing - Beck, E; Duckert, F; Ernst, M (Thrombosis and Haemostasis, 1961)
Congenital deficiency of Fibrin Stabilizing Factor (FSF) is the cause of both pathological haemostasis and poor wound healing. Experiments with fibroblast cultures were carried out to characterize the latter. Growth of the cultures in the patient’s plasma was quantitatively and qualitatively inferior as compared with the growth in normal control plasma, which contained FSF. Only by addition of normal plasma and purified FSF the poor cell growth was corrected. The necessity of fibrin present in the first stage of wound healing and possible modes of action of FSF in haemostasis and wound healing are discussed.